Effects of teacher's enhancement program on self-efficacy of public secondary home economics teachers in Iloilo City - Ortigas, Ma. Evelyn S.; Orlina, Elsa A. (2000)
The purpose of the study was to analyze how personal, family and work-related factors determine the self-efficacy levels of the public secondary home economics teachers in Iloilo City during the second quarter of the school year 1999-2000. It also aimed to determine the effect of the Teachers' Enhancement Program on the self-efficacy levels of the respondents. The experimental and descriptive methods of research were employed in the investigation. Seventy-two home economics teachers from seven high schools and four extension campuses in Iloilo City were involved and were randomized to compose the experimental and control groups. Results showed that the teachers' enhancement program effected change and significantly increased efficacy levels of the teacher-participants. There is no significant relationship between the perceived self-efficacy of the respondents and the personal and family-related factors. However, selected work-related factors were significantly related to teachers' efficacy. The teachers' training program and more of work-related variables rather than personal and family-related factors were significant predictors of teachers' efficacy.
Thesis (Ph.D. Home Economics)--University of the Philippines, Diliman.
Keywords: Home economics teachers -- Philippines -- Iloilo City; Teacher effectiveness -- Philippines -- Iloilo City